Bising di Area, Risiko di Telinga: Studi Multi-Level Kebisingan di Lingkungan Kerja Unit Usaha Mebel Kota Tanjungpinang - MF, M.Yusuf; Purnama, Irgi; Idris, M. Fadhil; Iskandar, Iwan (Jurnal Daur Lingkungan, 2025)
Noise is one of the important risk factors in the workplace that is often overlooked, particularly in small-scale furniture enterprises that have limitations in controlling the work environment. High noise exposure has the potential to cause hearing disorders as well as non-audiological complaints that impact worker productivity. This study aimed to analyze noise levels using a multi-level approach at the sound source, workers, supporting areas, and surrounding environment, and to examine their relevance to worker characteristics. The study was conducted in furniture enterprises in Tanjungpinang City with a quantitative descriptive design, using direct noise measurements in accordance with the Ministry of Manpower Regulation No. 5 of 2018 and a worker characteristics questionnaire. The findings showed that 78% of workers were exposed to noise exceeding the Threshold Limit Value (TLV), with the majority being in the productive age group (59%) and having more than two years of work experience (69%). A total of 31% of workers reported hearing complaints and 63% experienced non-audiological symptoms, while more than half of the workers (53%) did not use personal protective equipment (PPE). Multi-level analysis revealed that noise originated not only from machines but was also influenced by workspace layout, worker behavior, and the lack of environmental protection systems. In conclusion, noise control requires a comprehensive strategy through workspace layout adjustments, engineering controls on machines, increased compliance with PPE use, and protection of the surrounding environment. The contribution of this study emphasizes the urgency of a multi-level approach in protecting worker health, improving productivity, and supporting the sustainability of furniture enterprises. Keywords : Occupational Health and Safety; Occupational Noise; Multi-level Approach; Furniture Workers; Tanjungpinang